APPLICATION OF COGNITIVE BEHAVIOUR THERAPY (CBT) AND FAMILY PSUCHOEDUCATION (FPE) IN PATIENTS AT RISK OF SUICIDE: PENERAPAN COGNITIVE BEHAVIOUR THERAPY (CBT) DAN PSIKOEDUKASI KELUARGA PADA PASIEN DENGAN RISIKO PERILAKU BUNUH DIRI - wahyu Dini Candra susila; Yossie Susanti Eka Putri; Ice Yulia Wardani (Jurnal Perawat Indonesia, 2023)
Schizophrenia is a severe mental illness that causes disturbances in cognitive function, emotion, language, behavior and movement. One of the effects of severe mental disorders is suicide. Data shows that every 40 seconds, someone loses their life by suicide. The negative state of mind of patients at risk of suicide is usually a cognitive distortion. The purpose of this scientific paper is to provide an overview of the application of cognitive behavior therapy (CBT) and family psychoeducation to patients at risk of suicide using the Tidal model approach. Nursing actions were performed on 6 patients at risk of suicide. The method used is case series. The results show that giving cognitive behavior therapy (CBT) and family psychoeducation with the Tidal model approach can reduce suicide scores, reduce signs and symptoms and increase the ability of families and patients at risk of suicide with schizophrenia. Cognitive behavior therapy (CBT) and family psychoeducation are recommended to be carried out by psychiatric nurses to overcome the risk of suicide